Efforts to Preserve Woven Art by Utilizing Pet Rope Waste at “Cemoro Pitu Nganyam Budoyo” Event in Dayu Village, Karanganyar - Khasanah, Indah; Rahma, Faracha Nur; Nurazizah, Dwi Rahayu; Sasmita, Gilang; Khasanah, Laila Nur; Isnaningsih, Dini Salamah; Kusumawardani, Fahrillia Ayu; Rahayu, Ida Putri; Nugrahadi, Fariz Wiradasa Bhekti; Khoiri, Ilham; Hadibasyir, Hamim Zaky (Journal of Community Services and Engagement: Voice of Community (VOC), 2022)
This research was conducted in the village of Dayu, Gondangrejo District, Karanganyar Regency by promoting regional culture. The activities carried out were themed with the name Cemoro Pitu Nganyam Budoyo which aims to promote the tourism potential of Dayu village to the public. In addition, this activity is an increase in the strategy or efforts of the Dayu village government to develop cultural potential, which at the same time provides space for the community to improve the economy through marketing local culture such as culinary, crafts, agricultural products, and others. The methods carried out are in the form of committee formation, location determination, floor plan design, and event concept, progress of activity design, marketing and publication, implementation, and sustainable empowerment programs. KKNT students also participated in the event committee along with youths from Dayu village, the head of Grenjeng hamlet. Determining the plan design needs to pay attention to several things related to the concept of the event including the location of the main stage, invited guests, culinary tourism spots, visitor selfie spots, children's play spots (traditional toys), off road spots, free spots. Cultural market activities and pet rope workshops provide sustainable benefits for the Dayu community in addition to Cemoro Pitu which can become a new tourist destination, pet ropes can open up opportunities to increase the community's economy and new jobs. The work of pet ropes made by the Dayu community can support the village program, namely Dayu as a tourist village by making pet rope creations as typical souvenirs.